Concentration-dependent effects of carbon nanoparticles in gram-negative bacteria determined by infrared spectroscopy with multivariate analysis - Riding, Matthew J.; Martin, Francis L.; Trevisan, Júlio; Llabjani, Valon; Patel, Imran I.; Jones, Kevin C.; Semple, Kirk T. (Environmental pollution (1987), 2012)
With increasing production of carbon nanoparticles (CNPs), environmental release of these entities becomes an ever-greater inevitability. However, many questions remain regarding their impact on soil microorganisms. This study examined the effects of long or short multiwalled carbon nanotubes (MWCNTs), C60 fullerene and fullerene soot in Gram-negative bacteria. Attenuated total reflection Fourier-transform infrared (ATR-FTIR) spectroscopy was applied to derive signature spectral fingerprints of effects. A concentration-dependent response in spectral alterations was observed for each nanoparticle type. Long or short MWCNTs and fullerene soot gave rise to similar alterations to lipids, Amide II and DNA. The extent of alteration varies with nanoparticle size, with smaller short MWCNTs resulting in greater toxicity than long MWCNTs. Fullerene soot was the least toxic. C60 results in the most distinct and largest overall alterations, notably in extensive protein alteration. This work demonstrates a novel approach for assaying and discriminating the effects of CNPs in target systems. ► Unique biochemical changes occur in bacteria following exposure to particular carbon nanoparticle. ► Biochemical alterations become more pronounced with increasing concentration. ► Smaller nanoparticles result in greater biochemical changes ascertained by IR spectroscopy with multivariate analysis. Carbon nanoparticle-induced distinctive biochemical alterations in Gram-negative bacteria can be mechanistically fingerprinted using IR spectroscopy with multivariate analysis.